Persistent Air Leak - Anggita, Dwi; Wiriansya, Edward Pandu; Santoso, Arif; Putrawan, Harry Azka (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
In cases of pneumothorax in the chest tube, the presence of air in the pleural cavity that lasts more than 5 to 7 days can be suspected as a persistent air leak (PAL), especially if an increased amount of air is obtained accompanied by the appearance of bubbles in the water seal drainage (WSD) system. This is the most common complication after surgery (8–26%), although it can be primary spontaneous pneumothorax (PSP) (26%) or secondary spontaneous pneumothorax (SSP) (39%). One condition that often causes difficulties in PAL therapy is infection due to direct contact with the fistula. The presence of PAL is associated with higher morbidity and mortality, prolonged chest tube inserted, and longer hospitalization. Observations of air production in PAL are expected to occur spontaneously within 4 days, if the leak persists, pleurodesis is recommended. If it was possible, surgery is needed to close the leak. Bronchoscopy treatment is only recommended in special circumstances where surgery is contraindicated or the patient refuses the surgical procedure.